PENGEMBANGAN E-LKPD KALORIMETRI BERBASIS PROBLEM BASED LEARNING (PBL) MENGGUNAKAN LIVEWORKSHEETS - Syarani, Meylina; Suharman, Andi; Sanjaya, Sanjaya (UIN AR-RANIRY, 2025)
The lack of interactive teaching materials and students' difficulties in understanding concepts and calculations in calorimetry prompted the development of e-LKPD based on Problem-Based Learning (PBL) using Liveworksheets for class XI.1 students at Srijaya Negara High School, Palembang. This study aims to produce a valid, practical, and effective e-LKPD. The development follows the ADDIE model and includes Tessmer's formative evaluation stages: self-evaluation, expert review, one-to-one, small group, and field test. Data was collected through interviews with chemistry teachers, a needs analysis questionnaire administered to 35 students, a walkthrough with two experts who assessed the content, design, and pedagogical aspects, a practicality questionnaire administered to three students in the one-to-one stage and nine students in the small group stage, as well as pre-tests and post-tests administered to all 35 students. The validity test results showed an average validity score of 0.99, which falls into the very high category. The practicality of the e-LKPD in the one-to-one stage was 89.33% and in the small group stage was 91.82%. The effectiveness test results showed an N-Gain value of 0.80, which falls into the high category. Therefore, this e-LKPD is deemed valid, practical, and effective in enhancing students' understanding and engagement in calorimetry learning.